Methotrexate in Rheumatoid Arthritis: Effect on Blood, Liver and Renal Laboratory Parameters - Fuad Shaikh; Rabia Arshad; Fahad Azam; Nasim Karim (Journal of Bahria University Medical and Dental College)
Objective: To evaluate the effect of Methotrexate on blood, liver and renal laboratory parameters in patients having rheumatoid arthritis. Materials and Methods : A 24-week, single-blind, interventional study was carried out on 155 consecutive patients, aged 29- 70 years, diagnosed with rheumatoid arthritis. They received tablet Methotrexate, 10 mg (2.5 mg, 4 tablets) weekly, orally. Laboratory tests like hemoglobin level, total white cell and platelet counts, erythrocyte sedimentation rate, serum glutamic pyruvic transaminase and serum creatinine levels were recorded at the initial visit as well as at 6, 14 and 24 weeks follow-up visits. Results: At the end of 24 weeks hemoglobin level increased to 12.43 ± 0.92 grams per deciliter (g/dl) from a baseline of 10.76 ± 1.12 g/dl, white cell count fell to 7,142.46 ± 1332.23 per cubic mm (cmm) from 8,572 ± 1445/cmm, the ESR fell to 40.14 ±15.78 mm of Hg in 1st hour from 81.03 ±17.98 mm of Hg, the platelet count fell to 2, 33,738.10 ± 59,769/ cmm from 2, 90,278 ± 68,813/cmm, the SGPT levels increased to 55.29 ± 21.97 international units per litre (IU/l) from 31.67 ± 7.37 IU/l and the serum creatinine increased to 1.11 ± 0.14 mg/dl from 0.95 ± 0.16 mg/dl, all values being highly significant statistically (p<0.001). Conclusion: Methotrexate exerted significant effects on the blood, liver and renal laboratory parameters. These parameters may be utilized for monitoring the response and safety of methotrexate use in RA.